Development of simplified model for injection rate prediction of diesel injectors during transient and steady operation - Atac, Omer Faruk; Lee, Sanggwon; Moon, Seoksu (Fuel (Guildford), 2022)
•A simplified one-dimensional (1D) model is developed for injection rate prediction.•The accuracy of injection rate predictions is validated for short and long injection durations.•Nozzle discharge coefficient has a dominant role in the prediction for long injections.•The fuel viscosity has a critical effect on the flow development at the needle-seat area.•Thus, the needle-seat discharge coefficient can become a prominent factor for short injections. Determining the injection rate of the diesel injector during the transient short injection operations is a critical matter to enhance the combustion process by improving air/fuel mixture formation. In this regard, numerous injection models have been suggested in the literature to predict the injection rate accurately. However, such algorithms have not precisely predicted the rate of injection (ROI) in transient short injection events. In addition, most of those models require many input parameters to characterize hydraulic and mechanical subsystems in the injector, which can make them inconvenient to tune for different injector specifications, in other words not suitable for universal usage. Therefore, our study aims to develop a simple injection model that can predict injection rate precisely in the short and long injection durations considering relatively fewer input parameters. The model traces the pressure variation inside the sac based on the bulk modulus theory to predict nozzle exit velocity, thus the injection rate of the injector. In the algorithm, the bulk modulus of fuel (E) and discharge coefficients of the nozzle hole and needle seat (Cd,H and Cd,N) have been considered to vary rather than set constant during the injection process since such flow parameters would have a critical impact on the flow development at the transient stage, thus affecting the injection rate of diesel injectors. With this modelling strategy, the accuracy of the new model on ROI prediction was confirmed with acceptable model error for both short and long injection durations by validating against experimental results. To understand the effect of the new model scheme on ROI prediction, ROI results with the new model have been discussed by comparing it with the ROI results predicted with constant flow parameters.